Spaces for consumption - Miles, Steve (Sage, 2010)
"Spaces for Consumption offers an in-depth and sophisticated analysis of the processes that underpin the commodification of the city and explains the physical manifestation of consumerism as a way of life. Engaging directly with the social, economic, and cultural processes that have resulted in our cities being defined through consumption this vibrant book clearly demonstrates the ways in which consumption has come to play a key role in the reinvention of the post-industrial city. The book provides a critical understanding of how consumption redefines the consumers' relationship to place using empirical examples and case studies to bring the issues to life. It discusses many of the key spaces and arenas in which this redefinition occurs including shopping, themed space, mega-events, and architecture."-Provided by publisher.